Extractive Capital, Imperialism, and the Colombian State. (September 2018) - Sankey, Kyla
Since the turn of the century, Colombia has become increasingly dependent on mining exports to drive economic growth. While the surge in mining investments in Colombia and the problems associated with this form of economic development have received much attention from scholars and policy analysts, the common explanation is that the state has been undermined or eroded by emergent global forces. However, nation-states should be seen not as victims but as authors and enforcers of new processes of capital accumulation. The Colombian state has acted as the principal guarantor of the political and territorial conditions necessary for this form of extractive capitalism by reconstituting property and contract laws, signing free-trade agreements, reconfiguring the internal state apparatus. and expanding military forces. Desde el principio del siglo, Colombia se ha vuelto cada vez más dependiente de las exportaciones mineras para impulsar el crecimiento económico. Si bien el aumento de las inversiones mineras en Colombia y los problemas asociados con esta forma de desarrollo económico han recibido mucha atención por parte de académicos y analistas de políticas, la explicación común es que el estado ha sido socavado o erosionado por las fuerzas globales emergentes. Sin embargo, los Estados-nación deberían ser vistos no como víctimas sino como autores y ejecutores de nuevos procesos de acumulación de capital. El estado colombiano ha actuado como el principal garante de las condiciones políticas y territoriales necesarias para esta forma de capitalismo extractivo mediante la reconstitución de las leyes de propiedad y contratos, la firma de acuerdos de libre comercio, la reconfiguración del aparato estatal interno, y la expansión de fuerzas militares.